TANGGUNG JAWAB DAN KEWENANGAN BANK INDONESIA DALAM LIKUIDASI BANK - Sari Wiradiani, Ni Wayan; Ariawan, I Gusti Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 07, Juli 2013)
Indonesia’s Bank duty as the central bank is regulated in Law number 10 year 1998 about Banking. Indonesia’s Bank responsibility in the process of liquidation is to build and monitor the banking business in Indonesia. The research method used in this writing is normative and the problem approach applied is state approach, namely by investigating and analyzing the prevailing policies or regulations. Indonesia’s Bank responsibility is to save the banks when they are in critical conditions. While Indonesia’s Bank authorities are clearly regulated in the Law number 10 year 1998 about Banking, in article 37 paragraph ( 2) b.
Keywords: Responsibility, Authority, Liquidation, Bank